To solve the equation 6 = x + 23, we need to isolate the variable x.
Step 1: Start with the given equation:
6 = x + 23
Step 2: Subtract 23 from both sides:
6 - 23 = x + 23 - 23
-17 = x + 0
-17 = x
Step 3: Simplify:
x = -17
So the solution to the equation 6 = x + 23 is x = -17.
Note: Enter your answer and show all the steps that you use to solve this problem in the space provided.
Solve the following equation algebraically. Show your work.
6=x+23
this is what i did 6 - 2/3 = x + 2/3 - 2/3
(18/3) - (2/3) = x
(18 - 2) / 3 = x
16 / 3 = x
ANSWER: x=16/3 or 5.33
1 answer